What Is the Mechanism Underlying the Interleaving Effect in Category Induction: An Eye-Tracking and Behavioral Study - Ge, Yabo; Li, Fengying; Li, Xinyu; Li, Weijian (Frontiers in Psychology, 2021)
Interleaved practice, in which exemplars from different categories are intermixed within blocks, has been shown to enhance induction performance compared to blocked practice in which exemplars from the same category are presented sequentially. The current study’s primary goal was to evaluate explanations of why interleaved practice produces this benefit in category induction (known as the interleaving effect). We also evaluated two hypotheses, the attention attenuation hypothesis and the discriminative-contrast hypothesis, by collecting data on participants’ fixation on exemplars, provided by eye-tracking data, and manipulating the degree of discriminative-contrast. In experiment 1 and 2, participants were instructed to remember the style of 12 new artists in blocked and interleaved practice in fixed-paced and self-paced learning conditions respectively. We examined fixation durations for six positions (temporal sequence of exemplars presented in each block) using eye-tracking. The results indicated that fixation durations for the six relative positions did not differ significantly for blocked versus interleaved practice. In experiment 3, we manipulated the degree of discriminative-contrast to examine the impact on the interleaving effect in category induction. The results showed that the main effect of the degree of discriminative-contrast was significant, and performance in the high-contrast condition was significantly better than those in the medium-contrast and low-contrast conditions. Thus, these findings support the discriminative-contrast hypothesis rather than the attention attenuation hypothesis.